2021
DOI: 10.3390/ijms22073611
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Changes in Plants Grown in Salty Soil in Response to Inoculation with Halophilic Bacteria

Abstract: Soil salinity is an increasing problem facing agriculture in many parts of the world. Climate change and irrigation practices have led to decreased yields of some farmland due to increased salt levels in the soil. Plants that have tolerance to salt are thus needed to feed the world’s population. One approach addressing this problem is genetic engineering to introduce genes encoding salinity, but this approach has limitations. Another fairly new approach is the isolation and development of salt-tolerant (haloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Species of bacteria and fungi that live within plant tissues without causing harm to the plant are defined as bacterial and fungal endophytes, respectively. There has been increasing interest in the role of endophytes in plant adaptation to different adverse environmental conditions in a variety of ways, as outlined in Figure 1 [41,42]. It has been well-established that microorganisms associated with plants thriving under harsh environmental niches play a crucial role in their adaptations to these suboptimal conditions [43].…”
Section: The Relationship Between Bacteria and Plants In The Rhizospherementioning
confidence: 99%
“…Species of bacteria and fungi that live within plant tissues without causing harm to the plant are defined as bacterial and fungal endophytes, respectively. There has been increasing interest in the role of endophytes in plant adaptation to different adverse environmental conditions in a variety of ways, as outlined in Figure 1 [41,42]. It has been well-established that microorganisms associated with plants thriving under harsh environmental niches play a crucial role in their adaptations to these suboptimal conditions [43].…”
Section: The Relationship Between Bacteria and Plants In The Rhizospherementioning
confidence: 99%
“…Other researchers also showed bene cial effects of PGPR on growth of salt stressed alfalfa (Martinez et al, 2015;Ansari et al, 2019). For the interested reader, a review of mechanisms of salinity mediation on plants was recently completed by Miller and Nielsen (2021). While there are many studies examining the bene cial effects of soil microbes on alfalfa, few examine their use in tandem with conventional plant breeding.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method to enhance plant salinity tolerance is using green inoculants of plant growth-promoting rhizobacteria (PGPR), such as salinity-tolerant (halophilic) plant-associated bacteria. Miller and Nielsen summarized the molecular mechanisms involving the interactions between plants and salinity-tolerant bacteria and proposed their potential applications in improving crop production under salinity stress [ 11 ]. In the review by Ha-Tran et al, the authors identified that PGPR is a promising agent for seed bio-priming to enhance seed vigor and germination and the uniformity of subsequent seedling growth under salinity stress [ 12 ].…”
mentioning
confidence: 99%